Inducible clindamycin resistance among staphylococci isolated from clinical samples in an urban hospital of Dhaka City - Akhter, Shameem; Haque, SM Zahurul; Rahman, M Mushfequr (Ibrahim Medical College Journal, 2012)
Inducible clindamycin resistance was detemined in 200 clinical isolates of staphylococci from pus (53.5%) and wound swab (46.5%). The study was done from July 2009 to June 2010, in the Department of Microbiology, BIHS Hospital Dhaka. Inducible clindamycin resistance was demonstrated by placing an erythromycin disc (15 ìg) 15 mm apart from the edge of a clindamycin (2 ìg) disc in Mueller Hinton agar. When the clindamycin inhibited zone becomes D- shaped the organism was regarded as positive for inducible resistance (D- test positive). Out of 200 staphylococci, 20% had inducible clindamycin resistance, 5% had constitutive clindamycin resistance and remaining 75% was clindamycin sensitive. In case of methicillin resistant Staphylococcus aureus (MRSA), 48% had inducible clindamycin resistance while 11.5% was constitutively resistant to clindamycin and remainder were clindamycin sensitive. All clindamycin resistant strains were 100% sensitive to vancomycin and linezolid followed by gentamycin (42%) and tetracycline (42.3%). The findings demonstrated that a substantial proportion of staphylococci in our tertiary care hospital had inducible resistance to clindamycin. Ibrahim Med. Coll. J. 2011; 5(1): 6-8 Key words: Staphylococcus aureus; Inducible clindamycin resistance; Constitutive clindamycin resistance; D-test DOI: http://dx.doi.org/10.3329/imcj.v5i1.9853